Developing the evaluation criteria for the municipal solid waste systems - Krakow case study - Stypka, Tomasz; Flaga-Maryanczyk, Аgnieszka (Publishing House of Lviv Polytechnic National University, 2010)
The article presents the methodology which can help the decision makers in evaluation of different municipal solid waste disposal systems. The results of the well known computer Integrated Waste Management model (IWM-1) are usually too fragmented to allow the final decision. The authors present the scientific background of the IWM-1 results integration. The results of the IWM-1 model analysis have been integrated into some specific categories that originate from the field of the Life Cycle Analysis (LCA). The authors propose 11 environmental categories plus the general ones calculated by the IWM-1 model. The presented categories describe the environmental impact of the analyzed system and are far easier to identify and understand by the public and by the decision makers. The developed methodology has been applied for the City of Krakow. The authors analyze two Krakow municipal solid waste disposal systems. The first system has been in operation for the last few years. The waste is collected and disposed at the landfill site while recycling and composting are implemented only in a limited scale. The second system presents the potential ultimate solid waste option for Krakow, where the waste is sorted extensively, then a significant part of organic fraction is composted, and the rest of the waste goes to the incinerator. The presented analysis compares these two systems. The authors use the results from the IWM-1 models for both systems as the input data to calculate the proposed impact categories. The final outcome is presented as graphs with the detail description of each stage of generation. Наведено методику, за допомогою якої проводиться оцінювання різних муніципальних систем твердих побутових відходів. Результати відомої комп’ютерної комплексної моделі управління відходами (IWM-1), як правило, є занадто фрагментарними для прийняття остаточного рішення. Представлені наукові основи інтегрування результатів IWM-1. Результати аналізу моделі IWM-1 інтегровані в деякі специфічні категорії, що виходять з області аналізу життєвого циклу (АЖЦ). Запропоновано 11 екологічних категорій плюс одна загальна, розрахована за IWM-1 моделлю. Приведені категорії описують вплив проаналізованої системи на довкілля і є більш доступними для розуміння громадськістю та особами, що приймають рішення. Показано як розроблену методику застосовано на прикладі м. Кракова. Проаналізовано дві Краківські системи видалення твердих побутових відходів. Перша система перебуває в експлуатації протягом останніх кількох років. Відходи збираються і транспортуються на звалище, в той час як утилізація і компостування здійснюються лише в обмежених масштабах. Друга система представляє альтернативний варіант для м. Кракова, в якому відходи екстенсивно сортуються, тому значна частина органічної частини компостується, а решта спалюється. Представлений аналіз порівнює ці дві системи. Результати моделі IWM-1 для обох систем використані як вихідні дані для розрахунку запропонованих категорій впливу. Остаточні результати представлені у вигляді графіків, з детальним описом кожної стадії формування.
Розроблення критерію оцінювання муніципальних систем видалення твердих побутових відходів на прикладі Кракова
Keywords: regional municipal solid waste management modeling; LCA; моделювання управління муніципальними твердими побутовими відходами; АЖЦ